The Potential of Black Gluten and Red Rice in Rations on the Biological Values and Ideally Body Score of Healthy “Mini Rex Rabbit” - Sidik, Romziah (KnE Life Sciences, 2017)
The potentially of black gluten and red rice in rations was observed on performed of biological values and body condition score of Mini Rex Rabbits. Twelve male Mini Rex Rabbits averaging 2 months of age, body weight 1.95 kg were used as experimental animals. Four variations of ration: P0 a commercial, P1, P2, and P3 contains white, red, and black gluten rice, respectively. Research pattern of Complete Randomized Design include four group animals with three replications. The animals were treated by different ration as well as their treatment group during 8 weeks trials, and each animal received Alfalfa hay 10 g/h/d as a basic nutrient. Fecal and urine were collected every day along feeding trials and it’s analyzed by proximate analysis. Body weight and body condition score measured once a week.